Predicting underwater radiated noise of a full scale ship with model testing and numerical methods. (1st August 2018) - Li, Da-Qing; Hallander, Jan; Johansson, Torbjörn
Abstract: Full scale measurement, model testing and a hybrid CFD method were used to characterize the Underwater Radiated Noise (URN) of a ship at design speed. The CFD method consists of a multiphase Delayed Detached Eddy Simulation and the Ffowcs-Williams Hawkings acoustic analogy. The paper discusses the correlation of the noise spectra with the observed cavitation behavior and compares the measured full scale data with those predicted by the model testing and the CFD method. The comparison shows that the sheet cavity and Tip Vortex Cavitation (TVC) predicted by the model testing are in reasonably good agreement with the full scale observations. The pressure pulses are somewhat higher than the full-scale data. Overall, the predicted URN has a good correlation with the noise spectra obtained from the sea trial. The CFD method shows the potential to resolve turbulence eddy structures in the wake. It captures the dynamic development of sheet cavitation and the collapse and rebound of TVC as observed in the model test and the sea trial, but under-predicts the extent of TVC. The pressure pulses and tonal noise are in close agreement with the respective measured data for the first five orders of blade passing frequency. The method underestimates the broadband noise level in the frequency range 50–112 Hz where the TVC is expected to have an important contribution. The maximum under-prediction in this range is about 28 dB at 72 Hz. At frequencies above 200 Hz, the broadband noise becomes more and more under-predicted with increasing frequency. Highlights: Characterization of the underwater-radiated noise from a ship in full scale. Propeller cavitation, pressure pulses, radiated noise and their correlation were studied.. Sea trial, model testing and a hybrid CFD method using DDES and the Ffowcs-Williams Hawkings acoustic analogy are compared.